The effects of internal partition on indoor daylighting performance of student residential building in Ipoh, Perak / Khairul Azmi Mohamed, Asmat Ismail and Nur Azfahani Ahmad - Mohamed, Khairul Azmi; Ismail, Asmat; Ahmad, Nur Azfahani (Universiti Teknologi MARA, Perak, 2020)
The installation of an internal partition has resulted in lowering the illumination level inside a building. Therefore, this study is intended to evaluate the effects of several internal partition layout on indoor daylighting performance in student residential rooms. Several options of internal partition were simulated using Climate Based Daylight Modelling (CBDM) to suggest the effective partition layout to overcome low daylighting level inside the room at annual level. The findings indicate that the internal partition perpendicular to the window layout has been proven to have the highest annual daylight sufficiency in a student residential room in the tropics.